THE AU-PGE MINERALIZATION AT THE PAVLOVSK BROWN COAL DEPOSIT, PRIMORYE - Seredin V.V. (My University, 2004)
The paper describes the Au-PGE mineralization found in the coal-bearing depressions at the Pavlovsk brown coal deposit and at the depression borders. Precious metal mineralization occurs there at various levels of the Cenozoic sedimentary sequence and in the zones of hydrothermal alteration of rocks in the basement. Minerals of Au, Pd, and Pt found in coal layers (N1), in sandy-pebble sediments and enclosed fossil wood (N2), in deluvial clays, and in Late Cenozoic argillized explosive breccias are described. Mineral associations (native metals, alloys, halogenides, and sulfides) and associations of elements (coprecipitated lithophyllic, chalcophyllic, and siderophyllic ones) are similar in various rocks enriched with gold and platinoids. Thus, the stratiform ore mineralization in depressions is genetically related to the vertical zones of mineralized hydrothermally altered rocks at the depression borders and in the basement. Three stages in the formation of the Au-PGE mineralization at the Pavlovsk deposit are distinguished. An important factor in the ore formation were hydrothermal processes related to the outbursts of volcanic activity during the Miocene and Pliocene-Early Quaternary. It is proposed that hydrothermal Au-PGE mineralization at the Pavlovsk deposit is similar to the precious metal mineralization at the Serra Pelada deposit (Brazil) and the Lubin-Seroshovice ore district (Poland).